Development of mission control unit prototype for small class payloads / Amirul Syafiq Yahya - Yahya, Amirul Syafiq (2017)
Small satellites are experiencing rapid advancement where various missions are proposed. There are increasing trend in nanosatellite launches as the year progresses especially from 2012 to 2015. Since the introduction of low-scale satellites, many companies have emerged to support these projects, proven by establishment of many university spin-off companies worldwide. However, most of the commercial companies provide expensive on-the-shelf solution, which is a big disadvantage for the universities, specifically due to the limited source of funds to start up their own space program through the launch of their first satellite. In some countries, explorations in space-related research are still limited due to high cost of designing, developing, testing, and launching a satellite. To develop it in their own, knowledge in developing and integrating all the subsystems are very important. Therefore, this project proposed a low—cost platform, integrated with multiple sensors and Mission Control Unit (MCU) prototype that can be used to demonstrate the application and engineering concept of satellite. In this project, Arduino based control unit with real-time data logger that can control and retrieve scientific data from various sensors are developed on a 21) CubeSat platform for classroom demonstration purposes. The prototype will be able to perform many mission themes comprising earth observation, scientific, communications and technology over amateur radio frequency spectrum with the same protocol and modulation technique used by the low-cost Ham radio transceivers at ground station. This product has high commercialization potential, especially to schools and universities that would like to start their space program. The current prototype is designed to have flexibility of having any sensors integrated to it in future. It can be improved and integrated with other subsystems to produce a space qualified spacecraft model.